Reconstruction the Paradigm of Law and Justice on the Regulation of Right to Living Space of the Orang Rimba Tribe in Bukit Duabelas, Jambi Province - Muhamad Erwin (Faculty of Law, Sriwijaya University, Indonesia, 2018)
The dominance of the positivism law paradigm in the management of forest areas at Bukit Duabelas in Jambi Province has created a crisis for the rights of a living space of Orang Rimba’s tribe. Therefore, this requires further thoughts of the pattern of values and norms to be expansive with an emphasis on a quantity leading to a pattern of systemic values and norms em-phasizing the quality of humanist and ecological aspects which complement and maintain each other. This article explores the paradigm of state law and customary law on the regulation of the rights to a living space of Orang Rimba’s tribe, nomadic groups of people who live in wildwood, as well as ways of reconstructing it to fit the spirit of Pancasila